Sequential Failure Modeling and Analyzing for Standby Redundant System Based on FTA Method - Zhang, Min; Zhang, Zhijian; Zheng, Gangyang (Frontiers in Energy Research, 2018)
Fault Tree Analysis (FTA) has been a well-established and widely used method to deduct system failure scenarios for large complex systems like Nuclear Power Plants (NPPs). Redundant design is usually adopted in NPPs to improve system reliability, including parallel design and standby design. Sequential failures exist among the modules in a standby redundant system, which have not been detailed considered in FTA in industry, leading to an overestimation of system failure probability. Then if FTA is used to compare the reliability of the two designs, it will be found that parallel design is more reliable than standby, which is just the opposite of the conclusion from Reliability Block Diagram (RBD) analysis. To solve this problem, an improved Fault Tree methodology is proposed in this paper, using Priority-AND (PAND) gate and Condition-AND (CAND) gate to model the sequential failures. And the Boolean laws of logic is extended correspondingly for qualitative analysis, as well as the mathematic formulas for quantitative analysis. A case study is also presented to demonstrate the process and benefits for using the proposed approach